ENVIRONMENTAL DEGRADATION, TRANSNATIONAL CORPORATIONS (TNCS) AND DEVELOPMENT EQUATION IN THE NIGER DELTA - Prince Eze; Ewelie C. Justice (International Studies Journal)
Against the need to address developmental challenges in Nigeria, this study focusing on the Niger Delta andusing the Stakeholder theory as a framework for analysis examined how TNCshinder the development in the NigerDelta region through environmental degradation. Data collected through secondary sources revealed that activities and operations of oil TNCs negatively affect the environment. The findings of the study show that their unsafe operations destroy people's means of livelihood, damage the health of the environment and negatively impact the economic growth and development of the region. What is sadder in this situation is that the government has not been effective in monitoring and regulating their activities to minimize the negative impact of their operations on the environment, it is in this regard that it is recommended among other things, that government must insist that TNCs adopt international best practices and innovation in their operations, and beyond political speeches and conference communiqué government must also be proactive in enacting and implementing relevant environmental laws and policies that will help in minimizing the harm done to the Environmentenvironment.